2004
DOI: 10.1002/j.1939-4640.2004.tb02852.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Short CCR5 Messenger RNA Isoform in Human Spermatozoa

Abstract: It has recently been reported that the Regulated upon Activation of Normal T-cells Expressed and Secreted (RANTES) chemokine may exhibit a chemotactic effect on sperm. The RANTES chemokine acts on target cells by binding to the CCR5 receptor, which is present on the surface of various cells. Spermatozoa contain a complex repertoire of messenger RNAs (mRNAs) that may provide an insight into past events of spermatogenesis. The type and amount of CCR5 chemokine receptor transcript were investigated in spermatozoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Western blotting analysis confirmed the presence of both receptor proteins of the expected molecular weights. Our data are in agreement with the recent demonstration, by RT-PCR, that CCR5 mRNAs are present in ejaculated human spermatozoa (9,10), which represents the first evidence for the presence of CCR3 on the surface of human spermatozoa. We suggest that previous failure (26) to demonstrate significant CCR5 levels on human spermatozoa by flow cytometry, using FITC-conjugated monoclonal antibody, may have been due to technical problems.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Western blotting analysis confirmed the presence of both receptor proteins of the expected molecular weights. Our data are in agreement with the recent demonstration, by RT-PCR, that CCR5 mRNAs are present in ejaculated human spermatozoa (9,10), which represents the first evidence for the presence of CCR3 on the surface of human spermatozoa. We suggest that previous failure (26) to demonstrate significant CCR5 levels on human spermatozoa by flow cytometry, using FITC-conjugated monoclonal antibody, may have been due to technical problems.…”
Section: Discussionsupporting
confidence: 93%
“…Alfa‐chemokines (CXCs) and ß‐chemokines (CCs) are the two main subfamilies of chemokines, whose specific receptors are classified as a and ß chemokine receptors, respectively (8). More recently, it has been demonstrated that human spermatozoa contain mRNA coding for the CC‐chemokine receptors 1 and 5 (CCR1 and CCR5; refs 9, 10) that bind the ß chemokine regulated upon activation of normal T‐cells expressed and secreted (RANTES), and that RANTES has a chemotactic effect on human sperm (9). The presence of CX3CR1 mRNA and protein, a receptor for an additional subgroup of chemokines, has also been demonstrated in sperm; it has consequently been suggested that fractalkine, the corresponding physiological ligand, plays a role in maintaining sperm motility and regulating sperm chemotaxis (11).…”
mentioning
confidence: 99%
“…This RNA is organized in nonpolysomal messenger ribonucleoprotein complexes prior to exploitation during translation in round spermatids [Hecht 1990;Miller et al 1999]. A number of transcripts survive spermatid condensation and are present in human ejaculated spermatozoa [Miller et al 1999;Ostermeier et al 2002;Januchowski et al 2004;Jedrzejczak et al 2006]. These spermatozoal mRNA remnants might constitute a record of gene expression during spermatogenesis [Ostermeier et al 2004].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, DNA hypomethylation can be responsible for the transcription of endogenous retroviruses (HERV) (Januchowski et al, 2004).…”
Section: Discussionmentioning
confidence: 99%